Developing and Validating a Stability- Indicating Ultra Performance Liquid Chromatography Method for the Concurrent Measurement of Estradiol and Dydrogesterone in Bulk and Tablet Doses - Gorumutchu, Giri Prasad (Asian Journal of Pharmaceutics (AJP), 2025)
Purpose: A novel technique for quantitatively measuring estradiol and dydrogesterone (DYD) in pharmaceutical dose form is ultra-performance liquid chromatography which is easy, fast, accurate, sensitive, and repeatable. Materials and Methods: Using an acquity BEH (50 × 2.1 mm, 1.7 μm) column and a mobile phase comprising 45:55% v/v of NaH2PO4 and acetonitrile, chromatographic separation of estradiol and DYD was accomplished using a waters acquity high-performance liquid chromatographic system. At room temperature, a photodiode array detector was used for absorption at 260 nm to detect the 0.3 mL/min flow rate. Results: The results of a forced degradation investigation indicate that while less degradation was shown under hydrolysis (0.705%) and photolytic (0.927%) degradation conditions, considerable degradation was recorded under peroxide conditions (14.9%). The retention times for estradiol and testosterone were found to be 1.017 and 1.928 min, respectively. The linear calibration curves of (R2 = 0.99985 and R2 = 0.99972) were observed for the ranges of estradiol (2.5–15 g/mL) and testosterone (25–150 g/mL). The limits of detection and quantification were determined to be 0.03 μg/mL and 0.1 μg/mL, and 0.3 μg/mL and 1 μg/mL, respectively. It was discovered that all of the analytical validation parameters, including accuracy, linearity, and specificity, had percent relative standard deviation values <1%. The range of 101.0–99.2 was determined to be the recovery. When the purity angle is smaller than the purity threshold, the Empower software shows that the peak is homogeneous, as indicated by the purity flag “No.” Conclusion: In compliance with International Council for Harmonisation principles, the suggested approach was verified. It was discovered that the technique was easy to use, affordable, precise, accurate, and robust for studying the stability of estradiol and DYD as well as for quantitative analysis.